Voices and views : English language issues from different perspectives - Helale, Gabriela (2019)
The articles in this collection were produced within the framework of the MA program “Maestría en Inglés”, Facultad de Lenguas, Universidad Nacional de Córdoba, Argentina. They are based on selected MA theses and dissertations on Applied Linguistics and Literary Studies. The collection focuses on EFL teacher training, pronunciation assessment, academic writing, Critical Discourse Analysis and Literature.